The Medium Domination Number of Lexico Product of Two Paths P2 and Pn - Ramachandran, M.; Parvathi, N. (International Journal of Engineering and Technology, 2018)
Graph theory is a vibrant area in both applications and hypothetical. Graphs can be utilized as a demonstrating device for many problems of realistic consequence. It can be given out as mathematical models to identify a proper graph-theoretic problem. Domination is a hasty sprouting area of research in graph theory, and its various applications are distributed computing and societal networks. Duygu Vargor and Pinar Dundar [1] computed the idea of medium domination number exploited to scrutinize the pair of vertices. This paper study as explored the medium domination number of lexico product of two paths P2 and Pn.Â Â